Application of Process Hierarchy Analysis on the Internal Rating Credit Line Model for Islamic Banks - Astri Afrilia (Khazanah Sosial, 2020)
Banks in carrying out their business activities are always in contact with risk. Therefore, an internal rating system is needed so that the bank can select debtors and counterparts based on the level of risk. One of the bank's activities is the provision of credit lines for Islamic Bank in Indonesia. This study intends to formulate a credit line ranking model for Islamic Banks. This research uses quantitative methods using the Hierarchy Analysis Process method. An important finding of this study is the acquisition of an internal credit line rating model for Islamic Banks which can then be used to assist banks in determining the eligibility of an Islamic Bank to become a bank partner based on the level of risk.